Trade policy uncertainty as barrier to trade - Alberto Osnago; Roberta Piermartini; Nadia Rocha (World Trade Organization (WTO), 2015)
This paper studies the effects of trade policy uncertainty on the extensive and the intensive margins of trade for a sample of 149 exporters at the HS6 digit level. We measure trade policy uncertainty as the gap between binding tariff commitments under trade agreements (multilateral and regional agreements) and applied tariffs- what is also known as tariffs' water. Our results show that trade policy uncertainty is an important barrier to export. On average the elimination of water increases the probability of exporting by 12 percent. A one percent decrease of water also increases export volumes by one percent. We also find that the negative impact of trade policy uncertainty is higher for countries with low quality of institutions and in the presence of global value chains. Finally, our findings show that on average trade policy uncertainty is equivalent to a level of tariffs between 1.7 and 8.7 percentage points.
Keywords: F10; F13; F14; 330; binding overhang; tariffs; policy space; non-tariff barriers; World Trade Organization